Peradaban dan Pemikiran Islam pada Masa Turki Utsmani - Rahmida Putri; Haidar Putra Daulay; Zaini Dahlan (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This paper aims to uncover and review Islamic civilization and thought during the Ottoman period. The typeof this research is using a qualitative descriptive approach, namely the author describes what is contained in the history civilization and Islamic thought during the Ottoman Turkey, as well as the progress they have made by referring to or utilizing various natural methods. The type of research used is literature review. Researchers only utilizelibrary resources by carrying out reading, processing, and recording research materials. Only collect a few book references needed in research without going into the field. The results of this study are (1) there are several civilizations, namely the field of architectural art, the field of literature and prose, and one in the field of thought, namely wahdatul manifestation pioneered by Ibn ‘Arabi, (2) the progress and decline of the Ottoman Turkey